2021
DOI: 10.1021/acs.orglett.1c03131
|View full text |Cite
|
Sign up to set email alerts
|

Transient Directing Group Strategy as a Unified Method for Site Selective Direct C4–H Halogenation of Indoles

Abstract: A unified method for direct C4–H halogenation of indoles has been accomplished with the assistance of anthranilic acids as suitable transient directing groups. Exclusive site selectivity (one out of five potential reactive sites) as well as good functional group tolerance was obtained to install three kinds of halogen atoms (Cl, Br and I, respectively) by using inexpensive N-halosuccinimides (NXS) as halogen sources under mild conditions. Taking advantage of the rich functional groups in the product, a diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 49 publications
3
15
0
Order By: Relevance
“…The negative value for ΔG 2 −8.6 also implies that a monodentate acetate ligand in 13 is thermodynamically prone to participating in a ligand change reaction with HOTf to generate 14. Taken together, this analysis indicates that both the stronger coordination of the phenol carbamate in 5 than in 4 HOTf justify the exergonicity of the reaction 4 + HOTf → 5 + HOAc.…”
Section: ■ Results and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The negative value for ΔG 2 −8.6 also implies that a monodentate acetate ligand in 13 is thermodynamically prone to participating in a ligand change reaction with HOTf to generate 14. Taken together, this analysis indicates that both the stronger coordination of the phenol carbamate in 5 than in 4 HOTf justify the exergonicity of the reaction 4 + HOTf → 5 + HOAc.…”
Section: ■ Results and Discussionsupporting
confidence: 92%
“…Afterward, other researchers employed a similar methodology and installed a halogen onto various organic substrates. 4 Scheme 1 shows the commonly accepted mechanism for such a transformation. Accordingly, the reaction starts with the concerted metalation−deprotonation mechanism (i.e., the formation of chelated complex B, followed by ligand-directed C−H activation).…”
Section: ■ Introductionmentioning
confidence: 99%
“…In organic synthesis, the site-selective halogenation of the organic molecules is always one of the most fundamental classes. Aryl and alkyl halides are essential substrates in emerging research areas like electrochemical synthesis, photocatalysis, and transition metal catalysis. Additionally, aryl and alkyl halides are helpful to reduce the number of steps toward synthesizing natural products and active pharmaceutical molecules through C–C, C–N, and C–O bond-forming coupling reactions and nucleophilic substitution reactions. Specifically, the α-iodoenone derivatives are more reactive intermediate synthons. They are able to facilitate the synthesis of bioactive molecules, natural products (i.e., anthecotulide, prostaglandins, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, by taking advantage of trifluoromethylated alkynes as readily available versatile fluorinated building blocks for facile construction of various trifluoromethylated heterocycles, [12] we succeeded regiospecific incorporation of trifluoromethyl into isocoumarin scaffold by virtue of iridium‐catalyzed oxidative coupling of benzoic acids with trifluoromethylated alkynes [12a] . As a continuation of our research interesting in indole chemistry and fluorine chemistry, [12a,e,13] we speculated that transition‐metal‐catalyzed direct C−H functionalization of indole carboxylic acids with trifluoromethylated alkynes would provide a straightforward avenue for expeditious access to trifluoromethylated indolopyranone skeleton (Scheme 1c). Nevertheless, there lies several intricate challenges: (1) For indole‐3‐carboxylic acid, the site‐selectivity should be well‐controlled because the reaction could occur either on C2 or C4 positions; [14] (2) There are several competing side reaction should be avoided, such as decarboxylation [14,15] or direct addition of carboxylate to alkynes; [16] (3) In case of unsymmetric internal alkynes, good regioselectivity need to be dominated during the annulation process [10b,c,17] …”
Section: Introductionmentioning
confidence: 99%
“…Ag 2 O could provide comparable results, while AgNO 2 and Cu(OAc) 2 was inert for the transformation. Further reaction mediate evaluation revealed that proton solvent alcohol was favorable for the reaction (Table1, entries[13][14][15][16]). Both the yield and regioselectivity was improved in methanol (Table1, entry 13).…”
mentioning
confidence: 99%